RISK FACTORS FOR GOUT ARTHRITIS AMONG PATIENTS AT BUKIT KANGKA COMMUNITY HEALTH CENTER, SIOMPU DISTRICT, BUTON SELATAN REGENCY - Budi Prasetyo; Dila Saputri; Haslina; La Ode Asrianto (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Gout arthritis ranks among the ten most frequently reported diseases in the past three years, with multiple risk factors influencing its incidence. This study investigates the impact of dietary patterns, physical activity, and nutritional status on the occurrence of gout arthritis among patients at Bukit Kangka Community Health Center, Siompu District, Buton Selatan Regency.This quantitative research employed a case-control design. Purposive sampling yielded 102 participants, comprising 51 individuals with gout arthritis and 51 controls. Data collection involved questionnaires assessing dietary patterns, physical activity, and anthropometric measurements. The chi-square test and odds ratio (OR) were used to determine the magnitude of risk.The findings demonstrate that diet is a significant risk factor for gout arthritis, with an odds ratio (OR) of 3.143 (95% CI: 1.171–8.437). Physical activity is similarly associated with increased risk (OR: 2.670, 95% CI: 1.141–6.247), and nutritional status shows a comparable association (OR: 3.559, 95% CI: 1.541–8.219). In summary, individuals with a high-risk diet are approximately 3.1 times more likely to develop gout arthritis than those with a low-risk diet. Similarly, high-risk physical activity and adverse nutritional status increase the likelihood by approximately 2.6 and 3.5 times, respectively. These results suggest that adopting a low-purine diet, engaging in regular physical activity appropriate to individual capacity, and maintaining normal nutritional status are effective strategies for the prevention and management of gout arthritis.